NEW CULTIVAR OF PUMPKIN ‘ROMANTIKA’ SUITABLE FOR FARMING PRODUCTION, GARDENING LANDS AND PROCESSING - Т. M. Nikulina; D. P. Kurunina; E. A. Galichkina (Овощи России, 2018)
Research work is underway to create pumpkin varieties satisfying the requirements of consumers and the processing industry in Bykovskaya Melons and Gourds Experimental Breeding Station. The aim of the research was to develop pumpkin varieties with high content of dry matter and carotene, resistant to stresses and suitable for use in the food processing industry. Romantica is the variety resulted from breeding program, based on comparative characteristics of ‘Romantica’ and standard variety of Volzhskaya Seraya 92. New pumpkin variety ‘Romanctica’ exceeds the standard in contents of dry matter by 1.2%, sugars by 1.34%, sucrose by 1.73%, carotene by 46.44 mg%, yield by 0.5 t/ha. On the resistance to powdery mildew in artificial infection of sort of Romance has surpassed the standard by 11%, score at 0.4.